2020
DOI: 10.1002/tsm2.214
|View full text |Cite
|
Sign up to set email alerts
|

Compression enhances lower‐limb somatosensation in individuals with poor somatosensation, but impairs performance in individuals wth good somatosensation

Abstract: While research suggests that somatosensation contributes to elite athletic performance, little is known regarding the capacity of ergogenic aids (eg, compression) to enhance somatosensation. This study assessed the effects of compression socks on functional ankle somatosensory ability, and whether any effects depended on baseline somatosensation or ankle instability. Forty-two participants performed somatosensation testing using the active movement extent discrimination analysis (AMEDA) device, whereby the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Fifty-nine studies investigated the effects of compression garments on biomechanical and neuromuscular outcomes (Table S2 of the ESM). Studies used a range of participants from recreationally active [53,118,[137][138][139][140][141][142][143][144] to elite-level athletes [39,51,145,146]. A large portion of these studies (49%, n = 29) investigated the effects of compression garments on various kinematic variables including gait [52,95,104,127,132,145,147] and jumping technique [46,48,118,137], limb/muscle oscillatory patterns [39,48,54,121,143,148], range of motion [39,42,46,77,84,88,149,150], and joint angles [16,46,48,51,118,127,…”
Section: Biomechanical and Neuromuscular Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-nine studies investigated the effects of compression garments on biomechanical and neuromuscular outcomes (Table S2 of the ESM). Studies used a range of participants from recreationally active [53,118,[137][138][139][140][141][142][143][144] to elite-level athletes [39,51,145,146]. A large portion of these studies (49%, n = 29) investigated the effects of compression garments on various kinematic variables including gait [52,95,104,127,132,145,147] and jumping technique [46,48,118,137], limb/muscle oscillatory patterns [39,48,54,121,143,148], range of motion [39,42,46,77,84,88,149,150], and joint angles [16,46,48,51,118,127,…”
Section: Biomechanical and Neuromuscular Outcomesmentioning
confidence: 99%
“…Neuromuscular parameters were investigated in 33 studies, which comprised predominantly outcomes relating to muscle activation patterns as measured by surface electromyography (n = 20, 34%) [54, 55, 58-60, 63, 68, 75, 76, 82, 127, 140, 142, 143, 146-148, 152, 155, 156]. Additionally, studies have investigated the effects of compression garments on joint proprioception [4,53,121,144,149,157,158], balance and postural control [138,140], stability and lower body joint alignment [16], potentiated recruitment patterns and M-wave characteristics using electrical stimulation (n = 5, 8%) [59,87,159,160], reaction time [73], skeletal muscle metabolic state during exercise [161] and movement-related cortical patterns via electroencephalography [130]. The large majority of studies investigating kinematic outcomes relating to gait (i.e.…”
Section: Biomechanical and Neuromuscular Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was a great heterogeneity in the ability of participants to benefit from CG wearing to reduce inter-limb balance asymmetries. Previous studies about the effects of CG on functional somatosensory abilities have produced concordant findings while reporting a strong interindividual variability in responses to the wearing of CG in young healthy participants (You et al, 2004;Cameron et al, 2008;Broatch et al, 2021). After ranking participants according to their score in a movement discrimination task, these studies showed that only participants with poor lower limb somatosensation benefited from the wearing of CG to improve joint position sense, thus illustrating that the magnitude of the beneficial effects of CG wearing was inversely related to the participant's somatosensation at baseline.…”
Section: Discussionmentioning
confidence: 90%
“…Affordable external devices that interact with cutaneous receptors such as compression garments (CG) can also acutely improve balance control ( Kuster et al, 1999 ; Michael et al, 2014 ; Woo et al, 2017 ; Baige et al, 2020 ). The constriction provided by CG acts as a mechanically supportive framework that can activate interacting cutaneous mechanoreceptors that individually would not have been activated ( Baige et al, 2020 ), thus improving movement accuracy during tasks that include a large somatosensory component ( Hasan et al, 2016 ; Ghai et al, 2018 ; Broatch et al, 2021 ) and offering a potential benefit in reducing inter-limb balance asymmetries. Nevertheless, to our knowledge, no study has specifically investigated the effects of CG wearing on inter-limb balance asymmetries.…”
Section: Introductionmentioning
confidence: 99%